eDNA reveals spatial differences in species composition of protected rockfishes - Stephanie A. Matthews; Olivia M. Scott; Meredith V. Everett; Megan R. Shaffer; Elizabeth Andruszkiewicz Allan; Andrew O. Shelton; Gregory D. Williams; Abigail Wells; Krista M. Nichols; Ryan P. Kelly (PLoS ONE, 2025)
Rare species are difficult and time-consuming to detect, but environmental DNA (eDNA) methods can be used to increase data availability for monitoring and management. Here, we use the diverse rockfish species flock (genus Sebastes ) to demonstrate the utility of eDNA as a tool for detecting rare and difficult to observe species in the marine environment. We describe the identification of a phylogenetically informative gene region for eDNA metabarcoding which uniquely identifies 93 of the 109 Sebastes species currently described. We then use this assay to differentiate rockfish communities in field samples collected from two sub-basins within Puget Sound in Washington, USA. Across three field sampling platforms, we found that sample collection location (distance from seafloor) has substantial impacts on rates of detection and on the diversity of species detected, likely reflecting the habitat preferences of the target species. This metabarcoding region provides an important tool for rockfish monitoring, both within Puget Sound and across the North Pacific. More generally, this work speaks to the usefulness of eDNA data as a tool for the conservation and management of rare and difficult-to-distinguish species.